The Role of Information and Communication Technology in Education: Case of Eastern Mediterranean University - Bakare, Oluwatobi (My University, 2014)
ABSTRACT: Information and communication technology (ICT) is playing very important role in today Education. This main aim of this study is to investigate the role Information and Communication Technology in education in order to achieve better teaching and learning environment for the students. However, to reach that end, the researcher found out statistically how ICT has really impacted the student’s Educational life in Eastern Mediterranean University. Questionnaire was used for the experimental to accomplish this study. The groups are randomly selected consisting 197 participants at the Eastern Mediterranean University respectively. Data were analyzed using frequencies, Anova and T-test. The results showed that Using ICT in education makes school work more flexible. Students especially the third year students agreed ICT help them to do their work faster and better. The result of the study has showed that there is statistically significance difference at the level (0.05 level) of how students use Information and Communication Technology in their studies. The Students studying information Technology faced fewer problems than the students in other fields. Keywords: Distance Education, online learning, Information and communication technology, social networking, learning systems. ………………………………………………………………………………………………………………………… ÖZ: İletişim ve Enformtik (ICT) Teknolojisi bugünün eğitiminde çok önemli rol oynar. Bu çalışmanın ana araştırma konusu ICT teknolojisinin eğitimde oynadığı rolü araştırmaktır. Araştırmacı, burda ICT nin Doğu Akdeniz Üniversitesindeki öğrencilerin eğitim hayatlarını nasıl etkilediğini istatistiki değerlerle bulmaya çalışmaktadır. Bu araştırmada gerekli veriyi elde etmek için, Doğu Akdeniz Üniversitesinde okumakta olan, gelişi güzel seçilmiş, 197 öğrenci üzerinde bir anket uygulanmıştır. Elde edilen verilerin analizi için Frekans dağılımları, Anova ve T-testi kullanılmıştır. Elde edilen veriler ve analizleri doğrultusunda görülen o ki, ICT kullanımı öğrencilerin okul çalışmaları üzerinde daha olumlu ve esnek çalışma olanağı sağlamaktadır. Özellikle üçüncü sınıf öğrencileri ICT nin çalışmalarında çok yardımcı olup daha iyi ve hızlı iş çıkartmalarına yardımcı olduğunu bildirmişlerdir. İstatistiki analize dayalı olarak bu çalışmanın 0.05 seviyesinde öğrencilerin ICT kullanımlarındaki önemli fark görülmektedir. Araştırma aynı zamanda, ICT ana bilim dalında ki öğrencilerin bu konuda daha az problemle karşılaştığını da göstermiştir. Anahtar Kelimeler: Uzaktan Eğitim, online öğrenme, bilgi ve iletişim teknolojileri, sosyal ağlar, öğrenme sistemleri.
Master of Science in Information and Communication Technology in Education. Thesis (M.Ed.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technology in Education, 2014. Supervisor: Assist. Prof. Dr. Fahme Dabaj.
Keywords: Information and Communication Technology in Education; Education - Effect of technological innovations on - Eastern Mediterranean University - Cyprus, North; Educational technology - Information Technology - Eastern Mediterranean University - Cyprus, North; Educational innovations; Communication in education; Distance Education, Online Learning, Information and Communication Technology, Social Networking, Learning Systems